The Routledge handbook of sport in Asia - Fan, Hong 1957; Lu, Zhouxiang (Routledge international handbooks, 2021)
"This is the first book to offer a comprehensive overview of the history, development and contemporary significance of sport in Asia. It addresses a wide range of issues central to sport in the context of Asian culture, politics, economy and society. The book explores diverse topics including the history of traditional Asian sports; the rise of modern sports in Asia; the Olympic movement in Asia; mega sport events in Asia; sport governance and policy; gender, class and ethnicity in Asian sport, and Asia's sporting heroes and heroines. With contributions from 74 leading international scholars, it offers a new perspective on understanding of Asian sport and society, telling the story of how sport in this mega-region is coming together and reshaping the world in the process. It also provides readers with a wide lens through which to better contextualise the relationships between Asia and the world within the global sport community. The Routledge Handbook of Sport in Asia is a vital resource for students and scholars studying the history, politics, sociology, culture and policy of sport in Asia, as well as sport management, sport history, sport sociology, and sport policy and politics. It is also valuable reading for those working in international sport organisations"